Mechanical and fatigue properties of graphene oxide concrete subjected to sulfate corrosion - Wang, Xu; Zhang, Guoliang; Liu, Lang; Li, Yongguang; Kong, Hu; Zhang, Cheng (Frontiers in Materials, 2023)
Concrete structures usually have to experience some unfavorable environmental actions during their service life, leading to the mechanical properties degradation, moreover, cyclic loadings such as traffic loads, wind loads may further accelerate structural damage, therefore, improving durability of concrete is of vital for structures servicing in severe environment. Graphene oxide (GO), as a new nano-reinforced material, has ultra-high mechanical properties and large specific surface area as a concrete reinforcing material. This study entailed an examination of the properties of Graphene Oxide Concrete (GOC) with varying levels of GO incorporation (0, 0.02, 0.05, 0.08 wt%). It also encompassed an analysis of the fatigue properties of GOC under different stress levels and varying sulfate wetting and drying cycles. Additionally, the investigation delved into the degradation mechanisms affecting Graphene Oxide Concrete (GOC) when subjected to sulfate erosion conditions. Furthermore, the study assessed the mass loss of specimens and their fatigue life under diverse environmental conditions. The results showed that appropriate GO incorporations could enhance concrete's mechanical and fatigue properties after sulfate attack. In addition, scanning electron microscope (SEM) analysis showed that GO could adjust the aggregation state of cement hydration products and its own reaction with some cement hydration crystals to form strong covalent bonds, to improve and enhance microstructural denseness.